Penyuluhan Pemanfaatan Teknologi IoT dan AI pada Pertanian Melom Premium kepada Kelompok Satria Tani Hanggawana Kabupaten Tegal - Nurfahmi Fadlillah; Nurhadi Kamaluddin (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
The agricultural sector has a vital role in meeting national food needs, improving community welfare, and strengthening regional food security. However, the sector still faces various challenges, including land limitations, climate change, price fluctuations, and low production cost efficiency. Therefore, innovation is needed through the application of digital technology that is able to increase the productivity and sustainability of farming businesses. One of the solutions offered is the use of Artificial Intelligence of Things (AIoT), which is the integration of artificial intelligence (AI) with the Internet of Things (IoT) that allows agricultural systems to run more intelligently, efficiently, and scalably. This community service activity was carried out with the Satria Tani Hanggawana Farmers Group located in Kalisapu Village, Slawi District, Tegal Regency, with the main focus on premium melon cultivation. The method of the activity included material presentations on the concept of smart farming, the introduction of IoT-based sensor devices for monitoring temperature, humidity, and plant nutrition, field practices in greenhouses, simulations of the use of AI-based applications for crop prediction, and interactive discussions. In addition, material was also provided on simple agribusiness management, financial recording, and crop marketing strategies so that farmers are able to manage their businesses more professionally. The results of the activity showed a significant increase in participants' knowledge related to the application of AIoT in modern agriculture. Farmers not only understand the benefits of technology, but are also able to practice using tools and applications directly. The enthusiasm of the participants was reflected in their active involvement in discussions, willingness to try new technologies, and awareness of the importance of innovation to face agricultural challenges in the digital era.